Scoring Model for the Detection of Fake News - Pop, Mihai-Ionuț (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
Misinformation has always existed and has been promoted by groups of individuals, who share the same interests, in order to reach ideological, political or financial goals. In recent years, the emergence of the Internet and social platforms has opened a new and larger dimension in the dissemination of false content and information. With the help of these new technological means, the process of manipulation has evolved and reached a new level which materialized in the concept of fake news. The negative effects associated with this phenomenon have aroused interest among specialists, who are striving to find efficient instruments in order to combat the dissemination of fake information. In this context, I have developed a scoring model for the detection of fake news, which aims to combat the spreading of false information regarding specialized economic sectors, such as the energy field. Moreover, the model could also be implemented as an important instrument in the fighting against this negative phenomenon that can affect the way public figures, institutions, companies or industries are being perceived by the public opinion.